Development of a Measurement Instrument for Implementation of Experiential-Based Islamic Learning: Evidence of Feasibility - Kistoro, Hanif Cahyo Adi; Rachmaningtyas, Nur Anisyah; Jodi, Khairul Hamimah Mohammad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study focuses on the development of an instrument to assess the effectiveness of experiential-based Islamic learning at the tertiary level. This research is categorized as an instrument development study, with students serving as the respondents. The sampling method employed is a stratified technique, classifying students based on their experience and participation in experiential-based Islamic religious learning. A total of 93 students from undergraduate programs in Islamic Religious Education and Sharia Banking were deemed eligible to participate. The study successfully developed a quality instrument for measuring experiential-based learning, validated through construct analysis, as well as assessed for reliability. The instrument demonstrates a high validity (0.813) and good reliability (0.909). It is supported by the identification of key components that constitute experiential-based Islamic learning (EBL), which are categorized into three aspects: independence (SD), problem-solving (PCO), and experience as a learning resource (ELS). The results indicate a favorable tendency toward the successful implementation of each aspect. Based on these findings, it is recommended that educators focus on improving the design, execution, and evaluation of the learning process. Future researchers are encouraged to develop measurement models for assessing material understanding within the context of experiential learning.